Impact of Standardized Gestational Diabetes Screening on Maternal and Neonatal Health - Tahir Angez Khan, Zul-E-Huma, Muhammad Usman, Mumtaz Ali Lakho, Robina Qadeer, Naureen Ghani, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: To evaluate the effect of standardized gestational diabetes mellitus (GDM) screening on maternal and neonatal health outcomes among pregnant women receiving antenatal care at public sector hospitals. Methods: This cross-sectional study was conducted at DHQ Hospital Haripur and Bacha Khan Medical Complex, Swabi during the first half of 2023, from January to June. For the purpose of this study, 101 pregnant women in the 24 to 28 weeks of ‘gestation period were screened for GDM using either one step or two step oral glucose tolerance tests (OGTT)’. Information regarding the demographics and clinical details of the mother, along with the outcome of the pregnancy and the child, were gathered and analyzed. The significance of the results was assessed by means of a chi-square or t-test, considering p-values under 0.05 as statistically significant. Results: There is an increase in the prevalence of gestational hypertension, preeclampsia and cesarean deliveries in women with GDM. Infants with GDM mothers have increased risk of macrosomia, neonatal hypoglycemia and NICU admissions. Implementation of GDM-specific screening algorithms facilitated early diagnosis and treatment of GDM and enabled better maternal glucose levels thus decreasing the detrimental outcomes. Conclusion: The implementation of organized antenatal care has been associated with a decrease in the frequency of negative maternal and neonatal pregnancy outcomes. In order to mitigate the risks associated with pregnancy, early detection, accurate diagnosis, and timely intervention is paramount for enhanced nursing outcomes. Keywords: Gestational diabetes mellitus, standardized screening, maternal outcomes, neonatal complications, macrosomia, NICU admission, cesarean section